Indium tin oxide thin films prepared by ion beam assisted deposition technique at different ion beam currents - Meng Lijian (2008)
Indium tin oxide (ITO) films have been deposited onto glass substrates at room temperature by ion beam assisted deposition technique (IBAD) at different ion beam currents (80 mA – 120 mA). The effect of the ion beam current on films properties has been studied. The films prepared at low ion beam current (80 mA) show an almost amorphous structure. As the ion beam current is increased, films show a preferred orientation along the (222) direction. AFM measurements show that the surface RMS roughness of the film increases as the current goes up. The optical properties have been studied by measuring the transmittance. It has been found that the film prepared at 100 mA current has the highest transmittance. The optical constants of the films have been calculated by fitting the transmittance. The Hall measurements also showed that the film prepared at 100 mA current has one of the lower electrical resistivities. FTIR measurements show that the film prepared at 100 mA current has the highest infra-red reflectance. All the measurements show the 100 mA ion beam current can produce good quality ITO films.